2003
DOI: 10.1093/emboj/cdg083
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a U-insertion/deletion editing complex from Leishmania tarentolae mitochondria

Abstract: A multiprotein, high molecular weight complex active in both U-insertion and U-deletion as judged by a pre-cleaved RNA editing assay was isolated from mitochondrial extracts of Leishmania tarentolae by the tandem af®nity puri®cation (TAP) procedure, using three different TAP-tagged proteins of the complex. This editing-or E-complex consists of at least three protein-containing components interacting via RNA: the RNA ligase-containing L-complex, a 3¢ TUTase (terminal uridylyltransferase) and two RNA-binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
182
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(194 citation statements)
references
References 36 publications
12
182
0
Order By: Relevance
“…The REL1-TAP pull-down showed a minor amount of the endogenous REL1 in addition to the tagged REL1 (14). Similar results were obtained for another component of the REL1 subcomplex-the LC4 (MP63) protein (17).…”
supporting
confidence: 78%
See 4 more Smart Citations
“…The REL1-TAP pull-down showed a minor amount of the endogenous REL1 in addition to the tagged REL1 (14). Similar results were obtained for another component of the REL1 subcomplex-the LC4 (MP63) protein (17).…”
supporting
confidence: 78%
“…A comparison of the LC8-TAP polypeptide pattern with the previously obtained REL1-TAP profile (14) showed that in addition to the known bands seen in the REL1-TAP material, there were 4 previously undetected bands of varying intensity ( Fig. 2A).…”
Section: Tap Isolation Of Lc8-tagged L-complexmentioning
confidence: 70%
See 3 more Smart Citations